In vitro growth and cell wall degrading enzyme production by Argentinean isolates of Macrophomina phaseolina, the causative agent of charcoal rot in corn - Ramos, Araceli M. (2016)
Fil: Ramos, Araceli M. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Departamento de Biodiversidad y Biología Experimental (INMIBO). Buenos Aires, Argentina.